Flowing from East to West: A bibliometric analysis of recent advances in environmental flow science in China. (June 2021) - Hao, Zhuo; Rallings, Anna M.; Espinoza, Vicky; Luo, Pingping; Duan, Weili; Peng, Qidong; Gao, Yang; Viers, Joshua H.
Highlights: Chinese environmental flows research was characterized based on bibliometric analysis for the period 1967–2019. This body of research was compared to e-flows research trends within and outside of China. Prominent Chinese authors and important ideas in e-flows research were identified. This body of work helps identify prevailing trends in Chinese e-flows research. Abstract: Advances in water resources research in China has blossomed in recent decades. Although historically many Chinese scientific publications had been limited to regional, language-specific outlets, the more recent emergence of Chinese scholarship in water resources sustainability and engineering suggests that broader recognition within the scientific community is needed. In this study, we explore the recent evolution of Chinese environmental flows research through the bibliometric analysis of two prominent databases. This paper highlights trends in environmental flow publication rates, emerging areas of research, and citation networks for prominent authors in the Chinese context as compared to the global network of environmental flows research. Results indicate that China's environmental flows research developed rapidly over the past two decades (2005–2019) and that Chinese authors are among the most productive in the field (60% of the top 20 authors). However, based on the number of citations, few Chinese articles are among the most highly cited (5 out of 800). The field of environmental flows research has identified the need to minimize parochial boundaries, and this analysis suggests a rich, yet untapped, literature to promote scientific integration. Differences in journal selection, keyword choice, and lesser-known authors to readers outside of China were identified as potential limitations to broader global integration. This approach to systematic bibliometric analysis can be used to identify prominent authors and important studies such that new ideas in environmental flows research can flow across continental boundaries, from East to West, to accelerate global understanding of prevailing trends and best practices in river management